PENERAPAN ALGORITMA METODE NAÏVE BAYES UNTUK PENENTUAN PENERIMAAN BANTUAN PROGRAM INDONESIA PINTAR (PIP) - Priyanto, Imansyah; Dewanti, Elsa Mayorita; Tundo, Tundo; Nurdin, Muhammad; Kasiono, Roy (Jurnal Manajamen Informatika Jayakarta, 2024)
The Smart Indonesia Program (PIP) through the Smart Indonesia Card (KIP) is a government program offered in the form of direct education financing to students (6-21 years). KIP is an improvement part of the Poor Student Assistance (BSM) program since the end of 2014. The target of PIP at SMP PGRI 1 Cilacap is still not well targeted, due to the lack of criteria for KKS recipients. Therefore, the author added criteria for KKS recipients in the research. This research was created based on previously existing data, namely 100 training data and 9 test data using the Naïve Bayes data mining method and with 6 attributes, namely parents' occupation, number of dependents, parents' income, KIP recipients, KPS recipients, KKS recipients. The accuracy test results obtained were 88.89% and the Recall calculation was 85.71%.